2019
DOI: 10.3390/nano9121703
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-Derived Porous Activated Carbon for the Removal of the Chemical Warfare Agent Simulant Dimethyl Methylphosphonate

Abstract: Methods for the rapid removal of chemical warfare agents are of critical importance. In this work, a porous activated carbon material (C-PAC) was prepared from chitosan flakes via single-step potassium carbonate (K2CO3) activation for the prompt adsorption of dimethyl methylphosphonate (DMMP). C-PAC samples were prepared using different carbonization temperatures (350, 550, and 750 °C) at a constant K2CO3/chitosan ratio (1:2) and using different activator ratios (K2CO3/chitosan ratios of 1:0.5, 1:1, 1:2, and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Thanks to their high specific surface (usually > 2000 m 2 /g), activated carbons find a lot of applications involving adsorption process, such as air decontamination [69,70]. Since World War I and their use in protective mask [5], activated carbons have remained prototypical materials for the study of CWAs adsorption [22,71,72].…”
Section: Activated Carbons (Acs) and Activated Carbon Fibers (Acfs)mentioning
confidence: 99%
“…Thanks to their high specific surface (usually > 2000 m 2 /g), activated carbons find a lot of applications involving adsorption process, such as air decontamination [69,70]. Since World War I and their use in protective mask [5], activated carbons have remained prototypical materials for the study of CWAs adsorption [22,71,72].…”
Section: Activated Carbons (Acs) and Activated Carbon Fibers (Acfs)mentioning
confidence: 99%
“…After heat treatment at 250 °C-650 °C, a marked change can be seen on the CuOÀ C structure. This may be due to the presence of CS, which is an attractive material for the synthesis of carbon materials [32][33][34]. Additionally, CS efficiently chelates transition metal ions due to the presence of À NH 2 and À OH groups in its molecular backbone [35].…”
Section: Morphological Characterizationmentioning
confidence: 99%
“…Furthermore, there have been several attempts to create non-molecularly imprinted polymers using chitosan as the base material. For example, Yu et al reported DMMP absorption of 412 mg/g after carbonizing chitosan and submerging it in pure DMMP for 48 h. However, the experimental conditions provided are not realistic and performed in a laboratory setting. By using pure DMMP, there is no data on the selectivity of the material, and by leaving it submerged for 48 h, the breakthrough is also unknown .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yu et al reported DMMP absorption of 412 mg/g after carbonizing chitosan and submerging it in pure DMMP for 48 h. However, the experimental conditions provided are not realistic and performed in a laboratory setting. By using pure DMMP, there is no data on the selectivity of the material, and by leaving it submerged for 48 h, the breakthrough is also unknown . By carbonizing the chitosan, the complete structure is different from the structure reported in this paper.…”
Section: Introductionmentioning
confidence: 99%